Unity lost? Reframing ethnic relations in Lloyd Fernando's Green is the Colour - Lim, David C. L. (Taylor & Francis, 2010)
This essay reads Lloyd Fernando's Green is the Colour (1993) against the “lost” (forgotten, erased) but recently recuperated histories of ethnic unity in Malaysia to challenge the state's account which paints the past as a time of disunity and animosity between the ethnicities essentialized as “races”. Specifically, I reframe the racial violence of “May 13, 1969” at the heart of Green is the Colour to argue that the novel gives the event a much more radical treatment than has been critically acknowledged. Instead of presupposing racial difference as the natural and spontaneous cause of the violence, the novel, I show, unmasks as myth the account by the state which renders its own complicity invisible.